Association between central auditory processing mechanism and cardiac autonomic regulation - Regaçone, Simone F [UNESP]; Lima, Daiane Db [UNESP]; Banzato, Mariana S [UNESP]; Gução, Ana Cb [UNESP]; Valenti, Vitor E [UNESP]; Frizzo, Ana Cf [UNESP] (Springer Nature, 2014)
Background: This study was conducted to describe the association between central auditory processing mechanism and the cardiac autonomic regulation. Methods. It was researched papers on the topic addressed in this study considering the following data bases: Medline, Pubmed, Lilacs, Scopus and Cochrane. The key words were: auditory stimulation, heart rate, autonomic nervous system and P300. Results: The findings in the literature demonstrated that auditory stimulation influences the autonomic nervous system and has been used in conjunction with other methods. It is considered a promising step in the investigation of therapeutic procedures for rehabilitation and quality of life of several pathologies. Conclusion: The association between auditory stimulation and the level of the cardiac autonomic nervous system has received significant contributions in relation to musical stimuli. © 2014 Regaçone et al.; licensee BioMed Central Ltd.
Keywords: Auditory stimulation; Autonomic nervous system; Heart rate; P300